E-Computer Shop System (ECSS) / Lor Chee Loong - Lor , Chee Loong (2003)
The e-Computer Shop System (ECSS) is conceived to solve problems with typical business models which are inefficiency and lots of procedure in managing stock inventory. The e-Computer Shop System (ECSS) will serve to further enhance the current business model in search of a cost-effective and sophisticated solution. This project aimed for computer shop owner in order to assist them to meet the challenge and real business environment in the midst of today’s evolving world of information technology. The ECSS is able to manage all stock inventory in their own website as a way to promote their shop through internet. The ECSS is designed to auntomate the existing inventory management process running on SQL Server. This project will harness the full capabilities of Microsoft .NET Framework technology using Microsoft Visual Basic .NET (VB .NET) as system application language and Microsoft Active Server Pages .NET (ASP .NET) as dynamic web page language. Eventually, the successful implementation of the ECSS will create an automatic and paperless environment, revolutionizing the way of inventory management and internet promotion. Hopefully, it will be a generic system to suit all computer shop owner.